A questão social na literatura acadêmica brasileira em terapia ocupacional - Silva, Cíntia Viviane Ventura da (2019)
In a precarious social scenario characterized by structural inequality, the aim of this study is to analyze publications of occupational therapy in Brazil that approached and discussed social issues, considering structural inequalities in capitalist societies and parameterized by the extent (or lack of) social integration of individuals who need to offer their workforce to the labor market, i.e., by the extent of their integration into the work/job force and the extent of their social network support. The methodology of this study consists of an integrative literature review. A total of 37 terms were searched in titles of papers on four different sites: two Brazilian occupational therapy journals (Cadernos Brasileiros de Terapia Ocupacional and Revista de Terapia Ocupacional da USP) and two online databases (SciELO and LILACS). Searches on these databases were conducted combining the above mentioned terms with the term “occupational therapy”, since neither SciELO nor LILACS are specifically directed to publications on occupational therapy. This literature search was carried out in January 2018. Firstly, the following inclusion criteria were used: articles being published in Brazilian journals; first author having an undergraduate degree in occupational therapy (either ongoing or completed. Exclusion criteria were the following: publications other than articles (books, book chapters, editorials, etc.) and written in languages other than Portuguese. Of the 411 publications retrieved, 136 were duplicates, 32 were not articles, 29 were written in languages other than Portuguese, and there were 10 publications whose first author was not from the occupational therapy field. Subsequently, the abstracts of the remaining 204 articles were read. This stage of the review process included articles addressing social issues and/or related topics, and doubtful articles were read in full, leading to the exclusion of 154 articles. Therefore, this integrative review included 50 papers published from 2001 to 2017. Its results show that occupation therapy authors have been continuously and increasingly concerned about social issues, mainly those focused on the social branch of occupation therapy, called social occupation therapy. A total of 34 articles belonged to this branch, with publications from members of the METUIA Project showing great relevance (30 articles). Currently, poverty and inequality remain serious problems in Brazil, especially with regard to public policies required to address these issues. However, occupational therapy, particularly the branch directs its actions to the social field, has been seeking to tackle this reality by taking an ethical and political position that promotes people's empowerment and make them reclaim and exercise their citizenship: 27 papers identified citizenship as the articulating axis of occupational therapy practice in the social field. The present study revealed that the social branch of occupational therapy has been working to respond to and tackle the structural inequalities of the capital system, i.e., social issues, seeking for equal rights and individuals' autonomy. Conversely, it was observed that some occupational therapists, who should be directly interested in the processes of social inclusion and/or integration, do not take these issues into account.